Guías de estudio: una herramienta eficaz para el aprendizaje de las Ciencias Naturales en el quinto grado de Educación General Básica - Suquilanda Gueledel, Liz Nataly (2023)
The present research entitled: Study Guides: An effective tool for Learning Natural Sciences in the fifth grade of Basic General Education, has as a general objective: To determine the influence of the study guides in the learning of Natural Sciences in the students of the fifth grade, group "C" of "Marieta de Veintimilla" high school of Loja, city. For the development of the involving research process, the work of curricular integration had a mixed, descriptive approach, with a quasi-experimental design. Likewise, the methodology was based on scientific, statistical, analytical, synthetic and descriptive methods, and the techniques used were diagnostic evaluation in which a preand post-evaluative questionnaire was used to the students. In addition, the interview was based on a questionnaire applied to the teacher. The sample consisted of 19 students and one teacher. The evidenced results denote that the highest percentage of students were close to achieving learning, a considerable rate did not reach, the minority did not master the learning, and some mastered the knowledge. For this reason, a proposal for educational improvement was designed, and a workshop was presented with various activities directed based on the study guides. It strengthened the shortcomings found, showing favorable results that ensure its execution. This proposal brings fundamental benefits to improve the learning of Natural Sciences and make the student responsible for interpreting and building their own knowledge during the educational process. Keywords: study guides, teaching-learning, Natural Sciences, education.